Shelf-life Estimation of the Red Ginger Powder in Paper Kraft Packaging using ASLT Method Arrhenius Model - Saputri, Diah Ega; Ahmad, Usman; Pujantoro, Lilik (Jurnal Keteknikan Pertanian, 2023)
One form of processed red ginger to maintain its quality is dry powder. Therefore, a study is needed to determine the decrease in quality of red ginger powder in packaging during storage and to estimate its shelf-life. This research consisted of two stages, namely the first stage of making red ginger powder and the second stage of storing the ginger powder in packaging stored in an incubator using the accelerated shelf-life testing (ASLT) method. Quality analysis carried out were changes in moisture content, vitamin C, and color value. The results of drying and pulverizing red ginger produced red ginger powder with a water content of 10%, vitamin C content of 21.03 mg/100g and color value with a chroma value of 23.47. Based on the critical quality of red ginger powder, namely the chroma value, it can be concluded that the shelf-life of red ginger powder kraft paper packaging at 28 °C (room temperature) is 292 days and if it is stored at 30 °C then the shelf-life of red ginger powder in the same packaging material will be 212 days.